1986
DOI: 10.1177/106939718602000107
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Cross-Cultural Studies on Moral Judgment Development Using the Defining Issues Test

Abstract: Twenty cross-cultural studies on moral judgment development using the Defining Issues Test (DIT) were reviewed with respect to crosscultural validity, age/education trends, gender difference correlations with other psychological factors, religion, urban-rural, delinquency, and familial/societal factors. By and large, results indicate that the DIT has similar psychometric properties (factor structure, internal consistency, and reliability) and construct validity in non-American cultures. However, the rate of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
1
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 12 publications
1
14
1
7
Order By: Relevance
“…Regarding the lack of a gender difference, these findings were consistent with those of previous studies on gender differences and morality (Moon, 1986;Walker, 1985). However, these results were inconsistent with Franke, Crown, and Spake's (1997) meta-analysis, which found that women are more likely than men to perceive business practices as unethical.…”
Section: Differences In Students' Academic Levels Among Scenariossupporting
confidence: 93%
“…Regarding the lack of a gender difference, these findings were consistent with those of previous studies on gender differences and morality (Moon, 1986;Walker, 1985). However, these results were inconsistent with Franke, Crown, and Spake's (1997) meta-analysis, which found that women are more likely than men to perceive business practices as unethical.…”
Section: Differences In Students' Academic Levels Among Scenariossupporting
confidence: 93%
“…To ensure content validity, the constituent items representing the measurement constructs were drawn from previous research studies that used extended versions of the Technology Acceptance Model (Moon, 1986;Yi & Hwang, 2003;Yusoff, et al, 2010). 26 Likert-type scale questions representing the endogenous and exogenous constructs asked respondents on a scale of 1 (strongly agree) to 7 (strongly disagree) to indicate their extent of agreement or disagreement with a statement.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…While several DIT studies provide support for Kohlberg's universal proposition (Kracher et al 2002;Clarke et al 1996;Moon 1986;Snarey 1985) some studies show a difference between Western and Eastern cultures, with a bias towards Western cultures (Keller et al 2005;Al-Shehab 2002). Crosssectional studies in Kenya (Edwards 1975), Honduras (Gorsuch and Barnes 1973, cited in Parikh 1980, New Zealand (Moir 1974) and the Bahamas (White et al 1978) all provide support for Kohlberg's claim of universality.…”
Section: Stage Sixmentioning
confidence: 98%